2009
DOI: 10.1242/dev.039412
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II regulation duringC. elegansembryonic elongation:LET-502/ROCK, MRCK-1 and PAK-1, three kinases with different roles

Abstract: Myosin II plays a central role in epithelial morphogenesis; however, its role has mainly been examined in processes involving a single cell type. Here we analyze the structure, spatial requirement and regulation of myosin II during C. elegans embryonic elongation, a process that involves distinct epidermal cells and muscles. We developed novel GFP probes to visualize the dynamics of actomyosin remodeling, and found that the assembly of myosin II filaments, but not actin microfilaments, depends on the myosin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
206
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 136 publications
(221 citation statements)
references
References 58 publications
15
206
0
Order By: Relevance
“…Newly formed hemidesmosomes on both sides could later reorganize and align with each other during development to form mature fibrous organelles. Indeed, as discussed in the next section, recent studies have found a mechanism that specifically regulates basal hemidesmosome formation in C. elegans (Zahreddine et al, 2009). However, the detailed process of hemidesmosome assembly into fibrous organelles still awaits further investigation.…”
Section: Developmental Dynamicsmentioning
confidence: 95%
See 4 more Smart Citations
“…Newly formed hemidesmosomes on both sides could later reorganize and align with each other during development to form mature fibrous organelles. Indeed, as discussed in the next section, recent studies have found a mechanism that specifically regulates basal hemidesmosome formation in C. elegans (Zahreddine et al, 2009). However, the detailed process of hemidesmosome assembly into fibrous organelles still awaits further investigation.…”
Section: Developmental Dynamicsmentioning
confidence: 95%
“…Genetic analysis has revealed that embryonic elongation depends on proper establishment of epithelial polarity, adherens junction assembly, hemide smosome assembly, and cytoskeleton remodeling (Chisholm and Hardin, 2005;Labouesse, 2006). The initial phase of elongation depends mainly on the lateral epidermal cells (Diogon et al, 2007;Gally et al, 2009). The second part of elongation also requires muscle activity, although it is not known what kind of input muscles provide to the epidermis (Waterston, 1989;Williams and Waterston, 1994).…”
Section: Components Homolo-gies and Physical Interactions Of Hemidementioning
confidence: 99%
See 3 more Smart Citations